Higgs phenomenology in the flipped 3-3-1 model - Phạm, Ngọc Thư; Nguyen Tuan, Duy; Do Thi, Huong (Communications in Physics, 2024)
We investigate the Higgs phenomenology in the flipped 3-3-1 model with an assumption about the conservation of the B-L number. In addition to heavy scalar particles with masses at the new physics scale, there are three more light Higgs with masses at the electroweak scale, except for the SM-like Higgs. The new neutral CP-even scalar Higgs is identified as the scalar Higgs with a mass of 95 GeV, as hinted by CMS. For the light CP-even scalar, the characterization of Higgs coupling properties in terms of a series of Higgs coupling strength modifier parameters, which are defined as the ratios of the couplings of the Higgs bosons to particles to their corresponding SM values. We study several decay processes for the light CP-even scalar Higgs. Our numerical analysis is consistent with the experimental constraints.